Application of singular spectrum analysis method to forecast rice production in west sumatra: Artikel nazifatul azizah - Nazifatul Azizah; Fadhilah Fitri; Dodi Vionanda; Zamahsary Martha (UNP Journal of Statistics and Data Science, 2023)
The imbalance between the population and rice production will cause various negative impacts such as food crises and increasing poverty, so forecasting needs to be done to maintain food availability in the future. This study aims to determine the results of rice production in West Sumatra Province for 12 periods in 2023 using the SSA method. Based on the results of the analysis, rice production in 2023 for 12 periods tends to decrease compared to the previous year. Forecasting rice production using the SSA method with L=21 can be said to be accurate with a MAPE obtained of 17.69%.